Agogo Frozen Sdn. Bhd. / Muhammad Harmizi Ismail ... [et al.] - Ismail, Muhammad Harmizi; Zainol, Muhamad Zambri; Abdul Aziz, Mohd Fadzly; Zainul, Rozizan; Hashim, Hasdi; Ahmat Sharif, Baharuddin; Mohamad, Nooriskandar (Malaysian Entrepreneurship Development Centre (MEDEC), 2001)
Agogo Frozen Sdn. Bhd. is the only one new business that involves of the entire shear partner is from the UiTM Shah Alam student and already graduated. All of the partnership of this business is well knowledge in this profession. This companies totally supplier the meats that mean, this company will buy the fresh meats and sell the meats to the costumes in this business target. It's also because of the demand of the fresh meats from the costume in that area.